ANALYSIS OF ZIS PAYMENT METHOD PREFERENCES AMONG INDONESIANS - Deedat, Jagad; Paksi, Girindra Mega (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The use of digital platforms for collecting ZIS funds in Indonesia positively influences the payment method choices of muzakki and munfiq. This study aims to analyze how internal and external factors affect the preferences of muzakki and munfiq for three payment methods: directly to mustahik, through institutions, and via digital or online platforms. It employs an associative quantitative approach with a multinomial logistic regression model to compare the preferences of muzakki and munfiq. The research involved 318 respondents chosen through purposive sampling based on previous ZIS payment experience, with data collected via an online questionnaire and analyzed using SPSS. The results indicate that income, gender, trust, accessibility, and social influence are significant predictors of online payment choices. This study is expected to deepen the understanding of ZIS payment behavior, providing valuable insights for parties aiming to develop effective strategies.